Effect of Verbal Instruction on Motor Learning Ability of Anaerobic and Explosive Exercises in Physical Education University Students - Hermassi, Souhail; Sellami, Maha; Bouhafs, El Ghali; Schwesig, René; De Giorgio, Andrea (Frontiers in Psychology, 2019)
This study investigated the effect of motor learning with informational feedback in response to anaerobic exercises with and without motor learning tasks in handball physical education university students. Participants were randomly divided into an experimental group (EG: n=10) and a control group (CG: n=10). Measurements of T-half test, 15 m and 30 m sprints and ZIG-ZAG test were assessed in both groups before (T1), between (T2) four week and after (T3) 8-week intervention program, which included agility and speed teaching with (Experimental group; EG) or without (Control group; CG) informational feedback (i.e., verbal instruction). The test-retest reliability for all tests was excellent and the ICC ranged from 0.76 (ZIG-ZAG test) to 0.99 (Agility T-test). The interday measurement error was clearly below 1% in all tests (CV range: 0.2 - 0.8). Time effects for the agility T-test (p=0.012, p2=0.245) and sprint 15 m (p=0.035, p2=0.190) were found. For the agility T-test, a global interaction effect (p=0.001, p2=0.380) and a partial interaction effect were observed from T2 to T3 (p<0.001, p2=0.603). A large effect size (d=0.87), was recorded in EG group from T2 to T3. The second relevant (d≥0.5) effect size was calculated for the parameter sprint 30 m. The CG showed a significant deterioration from T2 to T3 (d=-0.60) regarding the sprint performance over 30 m. All other effect sizes were less than 0.44. The ZIG-ZAG test revealed the largest main and partial effect sizes for all parameters. The EG group showed the largest improvement (d=2.00) between T2 and T3. The results demonstrate that motor learning with informational feedback improves performances of agility T-test, sprint and ZIG-ZAG performance. It appears that a well formulated verbal instruction may induce performance enhancement in young trainee in educational environment.